2022
DOI: 10.3844/jcssp.2022.732.742
|View full text |Cite
|
Sign up to set email alerts
|

Combining SMOTE and OVA with Deep Learning and Ensemble Classifiers for Multiclass Imbalanced

Abstract: The classification of real-world problems always consists of imbalanced and multiclass datasets. A dataset having unbalanced and multiple classes will have an impact on the pattern of the classification model and the classification accuracy, which will be decreased. Hence, oversampling method keeps the class of dataset balanced and avoids the overfitting problem. The purposes of the study were to handle multiclass imbalanced datasets and to improve the effectiveness of the classification model. This study prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Using a feedforward and deep learning neural network model, (Pulickal, 2022;Jepkoech et al, 2022;Aburass et al, 2022) constructed practices in two passes and showed similarity across different applications. Based on a similarity index and the mean squared error of model behavior, (Panthong, 2022) calculated the peak signal-tonoise ratio. The results revealed existing methods for determining reliability.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Using a feedforward and deep learning neural network model, (Pulickal, 2022;Jepkoech et al, 2022;Aburass et al, 2022) constructed practices in two passes and showed similarity across different applications. Based on a similarity index and the mean squared error of model behavior, (Panthong, 2022) calculated the peak signal-tonoise ratio. The results revealed existing methods for determining reliability.…”
Section: Review Of Literaturementioning
confidence: 99%